CONTRIBUTION OF SYIRKAH ‘INAN TOWARDS THE ECONOMIC INDEPENDENCE OF THE COMMUNITY OF MAGELANG CITY, CENTRAL JAVA - Suraya Murcitaningrum; Moh.Tamtowi; M. Abdul Karim; Hazila binti Ismail, Nor (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This study is centered on exploring the implementation of Syirkah ‘Inan model as a strategy to build economic independence for lower-middle-class communities in Magelang City through organic fertilizer production. Therefore, a qualitative method and case study were adopted, with data collected through in-depth interviews, participatory observation, and documentation. The interview session was held with business actors, cooperation partners, local religious leaders, and related communities. The results showed that Syirkah ‘Inan functioned as an adaptive strategy to limited access to capital from conventional financial institutions. This was realized by facilitating the accumulation of interest-free collective capital through a fair and participatory partnership pattern. In addition, the internalization of Islamic values was ​​reflected through orientation towards blessings, halal, and social responsibility rather than profit. This was supported by the Selapanan Forum (meeting every 35 days), an institutional innovation that integrated educational, managerial, and spiritual dimensions. The practice of Syirkah ‘Inan produced transformational impacts in three dimensions, namely economic (increased income and financial stability), social (strengthening community solidarity), and spiritual (cultivating values ​​of honesty and trustworthiness). These attributes led to individual economic independence and community resilience that does not depend on external market mechanisms, rather on the endogenous strength of the community. Theoretically, the study reported the relevance of the Islamic jurisprudence principle in the context of modern economic. It showed that Islamic economic was an effective operational system starting from the micro-community level. As a result, Syirkah ‘Inan model was proven to be a theologically relevant and socially effective alternative for empowerment in building sustainable economic independence.